Examining the Concept of Protection (Defence) and Islamic Religious Cosmology in Vernacular Village Patterns in Gayo Highlands, Aceh - Wulandari, Elysa; Idawati, Dyah Erti; Nasution, Burhan; Edytia, Muhammad Heru Arie; Shara, Siti; haq, Zia Ul (Journal of Islamic Architecture, 2025)
Serule Village is the oldest Islamic settlement originating from the 17th century during the Aceh Sultanate and is classified as a Historical Cultural Heritage Village. Therefore, this research aimed to (1) identify the concepts of protection/defense found in the early vernacular settlement patterns of Serule, (2) analyze symbolic interpretations and Islamic values in the arrangement of Serule vernacular settlements, and (3) examine the harmonization of defense concepts with principles of Islamic cosmology in the embodiment of Serule vernacular settlements. Descriptive qualitative methods were adopted along with data collection techniques, such as observation, interviews, and literature review. The results showed that the configuration of Serule Village emphasized the importance of protecting living things and hydrological factors to avoid flooding. The linear functional spatial composition described a functional zoning system including agricultural land and graves (profane), villages (semi-profane),  Nurul Iman Mosque (central area), as well as gardens and mountains (sacred). Furthermore, the research showed that the composition of landscape elements and environmental characteristics proved a harmony between the need for physical protection (defense concept) and the Islamic values found in Serule village settlements. This discovery contributed to the development of vernacular theory regarding the concept of defense and Islamic religious values.